Analysis of the risk factors for incidental carcinoma of the prostate in patients with benign prostatic hyperplasia Análise dos fatores de risco para o diagnóstico do carcinoma incidental da próstata em pacientes com hiperplasia prostática benigna - Alberto Azoubel Antunes (Clinics, 2006)
PURPOSE: To determine the occurence of incidental carcinoma of the prostate, its characteristics, and the risk factors for this diagnosis in a group of patients surgically treated for benign prostatic hyperplasia. METHODS: The study comprised a retrospective analysis of 218 patients. After surgical treatment, patients with the finding of incidental carcinoma of the prostate were compared to those without this finding. The preoperative variables analyzed were patient age, digital rectal examination, PSA, PSA density, prostate volume, and preoperative prostate biopsy. We also determined the sensitivity, specificity, positive predictive value, and negative predictive value of digital rectal examination and PSA for the finding of incidental carcinoma of the prostate at surgical specimen analysis. RESULTS: Thirteen (6.2%) out of the 218 patients presented incidental carcinoma of the prostate. Eight (61.5%) of these tumors were classified as T1a and 5 (38.5%) as T1b. Only advanced age (P = 0.003) and the presence of a suspect digital rectal examination (P = 0. 016) were statistically related to the findings of the surgical specimen analysis. The sensitivity, specificity, positive predictive value, and negative predictive value for the diagnosis of incidental carcinoma were 23.0%, 96.6%, 30.0%, and 95.2% for a suspect digital rectal examination and 85.0%, 34.1%, 7.5%, and 97.2% for a PSA greater than 4.0 ng/mL. The accuracy for these methods was 92.2% and 37.1%, respectively. CONCLUSIONS: Advanced age and the presence of a suspect digital rectal examination represent the most important risk factors for the diagnosis of an incidental carcinoma of the prostate. However, the low positive predictive values reflect the weak correlations among these variables. OBJETIVO: Determinar a ocorrência do carcinoma incidental da próstata, suas características e fatores de risco para o diagnóstico em um grupo de pacientes tratados cirurgicamente para hiperplasia prostática benigna. MÉTODOS: O estudo compreendeu a análise retrospectiva de 218 pacientes. Após o tratamento cirúrgico, os pacientes com achado de carcinoma incidental da próstata foram comparados com os pacientes sem este achado. As variáveis pré-operatórias analisadas foram idade, toque retal, PSA, densidade do PSA, volume prostático e biópsia prostática pré-operatória. Também foram determinados a sensibilidade, especificidade, valor preditivo positivo e valor preditivo negativo do toque retal e do PSA para o diagnóstico do carcinoma incidental da próstata. RESULTADOS: Treze (6.2%) dos 218 pacientes apresentaram carcinoma incidental da próstata. Oito (61.5%) deles foram classificados com T1a e 5 (38.5%) como T1b. Apenas a idade avançada (p=0.003) e a presença de um toque retal suspeito (p=0.016) se relacionaram estatisticamente com este achado na peça cirúrgica. A sensibilidade, especificidade, valore preditivo positivo e negativo para o diagnóstico de carcinoma incidental da próstata foram de 23.0%, 96.6%, 30.0%, 95.2% para a presença de um toque retal suspeito e 85.0%, 34.1%, 7.5% e 97.2% para um valor de PSA maior que 4.0 ng/ml respectivamente. A exatidãos dois métodos foi de 92.2% e 37.1% respectivamente. CONCLUSÕES: A idade avançada e a presença de um toque retal suspeito representam os fatores de risco mais importantes para o diagnóstico de carcinoma incidental da próstata.